Investigating the Implementation of Classroom Assessment by Novice English Teachers - Karunia Eka Nafilatul Janah; Syafi’ul Anam (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2021)
Classroom assessment plays an important role in the success of English language teaching and learning in the classroom. Besides, implementing classroom assessment can be challenging for teachers since it needs a comprehensive process as well as adequate knowledge related to the subject matter. Some previous studies have proven that Indonesian novice teachers of English faced various challenges related to the real field of teaching that assessment is one of the challenges. Regarding the challenges of the assessment, this research is aimed at investigating the implementation of classroom assessment in assessing students’ English skills including its challenges and opportunities faced by novice English teachers. This research employed an open-ended questionnaire involving four female novice English teachers who have less than three years of teaching experience when this research is conducted. The results show that most of the novice English teachers implemented achievement tests that are often summative and used various tasks for assessing their students’ English skills. However, some of the novice English teachers could not answer the questions related to their practices of the assessment principles. Furthermore, the novice English teachers experienced challenges in implementing the classroom assessment such as when implementing peer-assessment, creating a valid grade in the assessment process, and not having enough time for the test preparation. Lastly, one of the novice English teachers involved in this research experienced the opportunities related to the implementation of classroom assessment as assessment not only can reflect the students’ learning progress, but also can know the weakness of the teaching.